2005
DOI: 10.1094/cc-82-0523
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Milling Product Yield Comparison with Reduced Levels of Bromelain and Varying Levels of Sulfur Dioxide

Abstract: Cereal Chem. 82(5):523-527

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…However, addition of SO 2 alone showed significantly (p \ 0.05) lower yield when compared to the enzyme treatment. These results were in agreement with those reported by Johnston and Singh (2005) who found that the addition of a combination of bromelain and SO 2 gave a higher yield of corn starch than the addition of SO 2 alone. Also, Perez-Carrillo and Serna-Saldivar (2006) reported a significant increase in starch yield from maize and sorghum treated with protease and SO 2 .…”
Section: Resultssupporting
confidence: 93%
“…However, addition of SO 2 alone showed significantly (p \ 0.05) lower yield when compared to the enzyme treatment. These results were in agreement with those reported by Johnston and Singh (2005) who found that the addition of a combination of bromelain and SO 2 gave a higher yield of corn starch than the addition of SO 2 alone. Also, Perez-Carrillo and Serna-Saldivar (2006) reported a significant increase in starch yield from maize and sorghum treated with protease and SO 2 .…”
Section: Resultssupporting
confidence: 93%
“…Enzymatic wet-milling was developed rapidly due to environmental friendliness. Johnston [12] used the protease to replace SO 2 to release the starch granules from the corn endosperm. Ramírez [13] reported that the use of enzymes in a modified procedure for wet-milling made SO 2 to reduce to levels sufficient to inhibit microbial activity and decreased the steeping time from 36 to 6 h. Alvoila [14] studied the effect of protease and transglutaminase on the microstructure and shelf stability of wheat dough and tortilla.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have used proteases to disrupt the linkages between corn proteins with some success. Some studies reported that proteolytic enzymes could replace or reduce the use of sulfur dioxide (Singh and Johnston 2002, 2004; Johnston and Singh 2001, 2004, 2005; Singh et al 2010). A cost model analysis showed that the enzymatic process enhanced the yields of corn wet‐milling products (starch conventional yield of 66.7% and enzymatic yield of 67.1%) and would reduce the production of sulfur by 12.6 million kilograms per year if adopted industrywide within the United States (Ramirez et al 2009).…”
mentioning
confidence: 99%